Бесконтактный комплексный многопараметровый вихретоковый контроль образцов слабоферромагнитных и ферромагнитных жидких сред - Себко, В.В.; Верба, А.Ю. (Електротехніка і електромеханіка, 2011)
The noncontact complex eddy-current multiparameter method of the control of the parameters of the weak-ferromagnetic and ferromagnetic liquid samples on the basis of two circuits of the thermal transformer eddy-current sensor (TES) is developed.